Wage rigidity, institutions, and inflation - Steinar Holden; Fredrik Wulfsberg (University of Oslo, Department of Economics, 2009)
A number of recent studies have documented extensive downward nominal wage rigidity (dnwr) for job stayers in many oecd countries. However, dnwr for individual workers may induce downward rigidity or 'a floor' for the aggregate wage growth at positive or negative levels. Aggregate wage growth may be below zero because of compositional effects, for example that old, high-wage workers are replaced by young low-wage workers. dnwr may also lead to a positive growth in aggregate wages because of changes in relative wages. We explore industry data for 19 oecd countries, over the period 1971-2006. We find evidence for floors on nominal wage growth at 6 percent and lower in the 1970s and 1980s, at one percent in the 1990s, and at 0.5 percent in the 2000s. Furthermore, we find that dnwr is stronger in country-years with strict employment protection legislation, high union density, centralised wage setting and high inflation.
Keywords: J3; J5; C14; C15; E31; 330; Wage inflation; downward nominal wage rigidity; OECD; wage setting; Lohnrigidität; Lohnbildung; OECD-Staaten